Annual migratory movement, apparent molt-migration, migration schedule, and diffuse migratory connectivity of Hermit Warblers - Hankyu Kim; Rodney B. Siegel; Jaime L Stephens; Joan C. Hagar; Brett J Furnas; Min-Su Jeong; Brenda C. McComb; Matthew G. Betts (Avian Conservation and Ecology)
Quantifying migratory connectivity and annual movement is key to sound conservation planning for migratory species. Hermit Warblers ( Setophaga occidentalis ) are an endemic-breeding species in the Pacific Northwest that winters in Mexico and the Central Americas. This species faces threats from mature forest loss and climate change throughout its range, but we know little about its migration ecology. To understand the annual movements and migratory connectivity of Hermit Warblers, we tracked 22 adult male Hermit Warblers from six breeding sites across the species’ breeding range using geolocators to examine migratory connectivity, spatiotemporal patterns, and migration routes. We found a high degree of mixing on the wintering grounds among birds from different breeding locations, indicating low migratory connectivity. However, birds breeding in Yosemite, the southernmost breeding location in our study, wintered farther east and south than birds from more northern breeding locations, providing weak evidence for potential chain migration. All birds showed much shorter and faster movements during spring migration than during fall migration. Birds arrived at breeding grounds from late April to mid-May and left breeding ranges from late June to mid-July. In fall, birds moved slowly from the breeding locations to montane regions in southern Oregon and California, which may indicate post-breeding molt before swiftly migrating to wintering grounds. Low migratory connectivity in this species implies that habitat and climate change across the broad wintering range may affect breeding populations throughout the species’ breeding range. A particularly compressed breeding schedule and departure of birds from the breeding grounds in early July may indicate that breeding is limited by a short window of favorable climatic conditions for breeding, which could signal heightened vulnerability under future climatic scenarios.